Examining Pictures : exhibiting paintings. - Bonami, Francesco; Fitzpatrick, Robert; Lampert, Catherine; Nesbitt, Judith; Museum of Contemporary Art, Chicago (London : Whitechapel Art Gallery, 1999)
Bacon, Francis ; Baldessari, John ; Baselitz, Georg ; Beecroft, Vanessa ; Berti, Simone ; Boulatov, Eric ; Brown, Glenn ; Celmins, Vija ; Currie, John ; Davenport, Ian ; Doig, Peter ; Dumas, Marlene ; Dunham, Carroll ; Gertsch, Franz ; Greenbaum, Joanna ; Guston, Philip ; Halley, Peter ; Hamilton, Richard ; Hirst, Damien ; Hockney, David ; Hume, Gary ; Immendorff, Jörg ; Kabakov, Ilya ; Kawara, On ; Khedoori, Toba ; Kiefer, Anselm ; Kippenberger, Martin ; Knoebel, Imi ; Kopystianskaya, Svetlana ; Kounellis, Jannis ; Krisanamis, Udomsak ; Landers, Sean ; Levine, Sherrie ; Manzelli, Margherita ; Marden, Brice ; Nader ; Nicolai, Carsten ; Orth, Dietrich ; Owens, Laura ; Peyton, Elizabeth ; Phaff, Vanessa Jane ; Pittman, Lari ; Polke, Sigmar ; Prince, Richard ; Raedecker, Michael ; Rayson, David ; Richter, Gerhard ; Ruscha, Ed ; Ryman, Robert ; Scheibitz, Thomas ; Singel, Rudolf ; Tuymans, Luc ; Twombly, Cy ; Warhol, Andy ; Weatherly, Royce ; Williams, Sue
geboortedata per kunstenaar
Engels
Examining Pictures : exhibiting paintings, Whitechapel Art Gallery, London, 7 May - June 27, 1999 ; Museum of Contemporary Art Chicago, July 24 - September 19, 1999
boek